2007
DOI: 10.1203/pdr.0b013e31813c9401
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor 2 Polymorphism Is Associated With Preterm Birth

Abstract: ABSTRACT:Evidence is increasing for a role of polymorphisms in maternal or fetal innate immune response genes in preterm birth. Toll-like receptors (TLRs) are important receptors in the innate immunity. The genotype distribution of two TLR2 single nucleotide polymorphisms (SNPs) and one TLR4 SNP were determined among 524 neonates and associated with gestational age (GA). Genomic DNA was isolated from prospectively collected blood samples and polymorphisms in TLR2 (T-16934A, RS4696480 and Arg753Gln, RS5743708) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 16 publications
0
37
1
Order By: Relevance
“…18 Our study concurs with the findings of the Finnish study. Krediet et al 19 found a significantly higher frequency of the TLR2 (rs5743708) polymorphism in premature neonates of o30 weeks gestation, which was not replicated in our study. Krediet and colleagues' study population was predominantly Caucasian and they excluded babies whose mothers had pre-eclampsia.…”
Section: Discussioncontrasting
confidence: 97%
“…18 Our study concurs with the findings of the Finnish study. Krediet et al 19 found a significantly higher frequency of the TLR2 (rs5743708) polymorphism in premature neonates of o30 weeks gestation, which was not replicated in our study. Krediet and colleagues' study population was predominantly Caucasian and they excluded babies whose mothers had pre-eclampsia.…”
Section: Discussioncontrasting
confidence: 97%
“…This potentially leads to aberrant innate immune responses, which may contribute to early preterm birth. 75 Individuals possessing the TLR4 co-segregating polymorphisms, Asp299Gly and Thr399Ile, are hyporesponsive to lipopolysacharide and are more susceptible to Gram-negative bacterial infections. 73,76,77 Those fetuses carrying the low-expression alleles of these receptors would hypothetically be more susceptible to die either by uncontrolled parasite replication/invasion or impaired trophoblast growth.…”
Section: Immune Response In Acquired Toxoplasmosismentioning
confidence: 99%
“…[34][35][36] Several studies have shown an association between preterm birth and TLR polymorphisms. [37][38][39] Animal studies have demonstrated a strong link between the TLR4 agonist LPS and brain injury, in fetal and newborn animals. 40 The direct involvement of TLRs has been examined in newborn animals.…”
Section: Tlrs and Perinatal Brain Injurymentioning
confidence: 99%